FACILITIES PROVIDED FOR CHILDREN WITH DISABILITIES IN INCLUSIVE SCHOOLS TO PARTICIPATE IN THE ACTIVITIES - Dr Mohanasundaram, P.Kamaraj (International Journal of Advanced Science and Technology, 2020)
United Nation sets the goal of Education for all includes children with disabilities along with other children who are left out from the school program across the levels (Biwako Millennium Development Goal 1994). The population of persons with disabilities are 2.8 crores (NSSO 2011), the types of persons with disabilities reported in the senses are visual, hearing, speech, loco-motor, Intellectual and Multiple disabilities. The United Nation’s Convention on the Rights of Persons with Disabilities (UNCRPD), 2007 directs all the member counties to provide education on Right basis to children with disabilities. Achieving the Millennium Development Goals is impossible without improving access and providing facilities for children with disabilities to learn in the school environment. The National flagship program of Sarva Shiksha Abhiyan (SSA) and its framework clearly mentioned that all the children with special needs, irrespective of category, degree of disability and their functional limitations the education is provided in an appropriate environment. The result show that all the school are having the ramp and toilet facilities under the resources of infrastructure. 89.61% of the Schools are providing the facilities of Social benefits. It is reported that the specialised services are provided based on the needs of the children, 72.19% of the schools are providing the facilities of text books as resource materials to the children with disabilities. It is inferred that there is no significant change in providing facilities to the children with multiple disabilities in the inclusive school.